Pemberdayaan Kader Posyandu Lansia Melalui Public Speaking Dalam Pencegahan Hipertensi Di Wilayah Kerja Puskesmas Padang Luar - Naifah Isma Balqis; Evi Maria Lestari Silaban; Erick Zicof; Sumihardi Sumihardi; Nindy Audia Nadira (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2026)
Background: Hypertension is one of the most common non-communicable diseases among the elderly. In the working area of Padang Luar Public Health Center, 2,171 elderly people were recorded as having hypertension in 2024. One of the barriers to hypertension prevention is the limited ability of Posyandu cadres to deliver health education effectively, thus cadre empowerment through public speaking training is required. Objective: To explore in depth the empowerment of Posyandu cadres related to public speaking skills in hypertension prevention efforts. Methods: This study employed a qualitative approach with a case study design. Informants consisted of elderly Posyandu cadres, elderly participants, the person in charge of health promotion and NCD programs at Padang Luar Public Health Center, and a public speaking expert. Data were collected through in-depth interviews, observation, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. Results: Public speaking training improved cadres’ understanding of the importance of verbal communication in health education. Cadres became more confident, able to organize materials, manage their voice, and adjust their speaking style according to the elderly’s condition. In addition, cadres were more active in interacting and building open communication, while the elderly began to show healthier lifestyle changes by applying the CERDIK program. Conclusion: Public speaking training supports the empowerment of elderly Posyandu cadres in hypertension prevention. Such training should be conducted in a practicebased manner with support from public health centers, local government, and related institutions.